1959
DOI: 10.1021/ac50164a028
|View full text |Cite
|
Sign up to set email alerts
|

New Columnar and Mixed-Bed Ion Exchange Methods for Surfactant Analysis and Purification

Abstract: together with the precipitation of the rare earth oxinates with the lanthanum carrier is at least 97% (S). Because the recovery in either the double oxalate or fluoride precipitation was essentially 100%, the over-all recovery of the rare earths should be about 97%.This value was checked by analyzing duplicate 10-gram samples of beryllium to which was added europium-152-154 after dissolution. An average 98% recovery of the tracer activity was found in the final oxide residue. With larger 28-gram samples, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1961
1961
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…The CMC is a function of alcohol concentration (17,18) and is, in fact, inversely proportional a t lower alcohol concentrations. This explains the necessity for alcoholic eluants in the analysis of detergents and shampoos (2)(3)(4)(5)(6). Kewburger (2) found that alkyl sulfates when adsorbed onto weakly basic ion exchange resins could not be eluted by (1 f 9) ammonium hydroxide, dilute hydrochloric acid, ethyl alcohol, or an aqueous solution of ammonium hydroxide and ammonium carbonate.…”
Section: Discussionmentioning
confidence: 99%
“…The CMC is a function of alcohol concentration (17,18) and is, in fact, inversely proportional a t lower alcohol concentrations. This explains the necessity for alcoholic eluants in the analysis of detergents and shampoos (2)(3)(4)(5)(6). Kewburger (2) found that alkyl sulfates when adsorbed onto weakly basic ion exchange resins could not be eluted by (1 f 9) ammonium hydroxide, dilute hydrochloric acid, ethyl alcohol, or an aqueous solution of ammonium hydroxide and ammonium carbonate.…”
Section: Discussionmentioning
confidence: 99%
“…The authors acknowledge the information provided by Charles Keith regarding his preliminary attempts to use purine complexation for the countercurrent separation of closely-related polycyclic aromatic hydrocarbons. LITERATURE CITED (1) Biltz, H., Strufe, K., Ann. 413,197 (1916).…”
Section: Acknowledgmentmentioning
confidence: 99%
“…These compositions often contain both water-soluble and oil-soluble surfactants to obtain a better balance of properties, and in addition, usually contain other nonionic, nonsurfaceactive materials, such as hydrocarbon oils, fatty esters, glycols, and unreacted raw materials from surfactant manufacture. The removal of ionic surfaceactive agents present in the composition is conveniently accomplished by ion exchange (1,7,8,10,12), but all the nonionic surfactants, together with any nonionic nonsurfactant material, pass unadsorbed through the ion exchanger. The analysis of this mixture of nonionic surfactants and related materials is usually a difficult task and, in spite of its common occurrence, only a few attempts have been made to systematize the analysis of this type of mixture.…”
Section: Compositionsmentioning
confidence: 99%
See 2 more Smart Citations